Hoffmannia uxpanapense (Rubiaceae), a new species from southern Veracruz and Oaxaca, Mexico - Castillo-Campos, Gonzalo; Bautista-Bello, Alma Patricia (Instituto de Ecología, A.C., 2017)
Background and Aims: The revision of herbarium specimens of Hoffmannia (Rubiaceae) and the extensive exploration by the authors has resulted in the discovery of new species within this genus. Hoffmannia uxpanapense Cast.-Campos and Bautista-Bello is described and illustrated as a new species of the Rubiaceae family from southern Mexico, collected in the evergreen tropical forest of Uxpanapa in Veracruz and Oaxaca.Methods: The specimens of the genus Hoffmannia of the state of Veracruz were studied, a matrix of morphological data was elaborated, and a cluster analysis was carried out to differentiate the species and to detect their similarities.Key results: The specimens identified as “H. wendtii” presented different morphological characters to the species already described in this genus. As this name has not been published, it was considered as a new species that still needs to be formally described. This species shows similarities with H. cuneatissima, H. minuticarpa and H. arqueonervosa. Nevertheless, H. uxpanapense differs by being a climbing shrub, with larger internodes on the stem, larger inflorescences and a greater number of white flowers per inflorescence.Conclusions: Hoffmannia uxpanapense belongs to a group of endemic species of Mexico (H. cuneatissima, H. minuticarpa and H. arqueonervosa), and this new taxon is considered as endemic of the southern zone of Veracruz and Oaxaca.